(untitled) (Patan Pragya, 2021)
This research article, “Analysis of Trends and Management Pattern of Educational Aid in Nepal: An Empirical Analysis” aims to analyze the trends and management pattern of education aid in Nepal. Aid is the essential means to remove the bottleneck of development in Nepal. Since 1952 AD international donors have been supporting education sector reforms in Nepal with individual basis. Aid program Education for All (EFA), (2004-2009 AD) was established with donors and Nepal Government Joint Financing Agreement (JFA) for the school education reform. Then after, EFA (2001-2015) established education aid for the reform of primary education in Nepal. This research used the secondary data from the different sources of information and used the descriptive research design for data analysis. The researchers concluded that the educational aid trend is in increasing way in each year, only effective management will fulfill the target and increase the effectiveness of the educational aid in the context of Nepal.